Indonesian Tourism on Australian Websites: Mapping Major Issues with Online Field Theory - Sidiq Hari Madya (JSW (Jurnal Sosiologi Walisongo), 2023)
Australia is very important to Indonesia’s tourism recovery strategies after the COVID-19 pandemic. This study examines tourism issues in Indonesia as represented by Australian websites. By mapping actors and issue networks in Australian sites, this study identified the status and behavior of actors in online networks. This study applies a Bourdieusian framework adapted to an online setting called online field theory. Applying web data to study the behavior of actors or organizations, this study combined the hyperlink network and content analysis. It has been found that tourism policies and tourism impact on the economy in Indonesia is a major concern for Australian actors. The web narratives indicate that the COVID-19 pandemic contextualizes the emergence of major issues and prominent actors dealing with the issues. A map of the hyperlink network confirmed the structure of the fields in which privileged actors in Australia, such as the government and the media, are more central in framing and diffusing the issues. It is argued that issue formation and adoption on the web reflect multiple Australian interests to Indonesia’s tourism.